A versatile synthesis of αGalCer and its analogues exploiting a cyclic carbonate as phytosphingosine 3, 4-diol protecting group. (15th January 2019) - Panza, Luigi; Compostella, Federica; Imperio, Daniela
Abstract: A convenient synthetic strategy to αGalCer and some relevant analogues by using a handily protected phytosphingosine is reported here. The conversion of the phytosphingosine amino group to azide and the protection of 3, 4-diol as cyclic carbonate group, cleavable in mild basic conditions but resistant to acidic treatment, afforded quickly an excellent glycosyl acceptor. Its glycosylation with a proper galactosyl donor, gave a versatile intermediate in high yield and excellent stereoselectivity. To demonstrate the potentiality of the intermediate, three immunologically relevant compounds were chosen as model targets: αGalCer, dansyl alpha-galactosylceramide and 7DW8-5. These products were easily obtained in few steps and high yields to validate the synthetic route. Graphical abstract: Highlights: Development of a new phytosphingosine acceptor through carbonate diol protection. Highly stereoselective glycosylation reaction to α-Galactosylceramide precursor. Access to glycolipid analogues through the flexibility of the synthetic approach.